Multistable Electro-optical Modes in Ferroelectric Liquid Crystals - Hegde, Gurumurthy; Pozhidaev, Eugene; Chigrinov, V. G.; Xu, Peizhi (Blackwell Publishing Ltd, 2009)
Multistable electro-optical modes exist under certain conditions in ferroelectric liquidcrystal (FLC) cells, which means that any light-transmission level can be memorized after the driving voltage is switched off. The multistability is responsible for three new electro-optical modes with different shapes of the gray-scale curve that can be either S-shaped (double or single dependent upon the applied-voltage pulse sequence and boundary conditions) or V-shaped dependent upon boundary conditions and FLC cell parameters. The origin of these modes will be described.